FEEDING POTENTIALITY OF COCCINELLA SEPTEMPUNCTATA ON THREE DIFFERENT APHID SPECIES AND ITS MOLECULAR IDENTIFICATION BASED ON MITOCHONDRIAL COI GENE SEQUENCE - SUSMITA SARKER; ABDUL JABBER HOWLADER; ABU FAIZ MD. ASLAM (The Bioscan, 2019)
Predatory efficacy of coccinellid beetle, Coccinella septempunctata (Coleoptera: Coccinellidae) on three important aphid pests was studied in laboratory. The number of A. craccivora, A. fabae and A. gossypii consumed by 1st, 2nd, 3rd and 4th instar C. septempunctata larvae were 16.67 ± 0.58, 23.33 ± 1.53, 41.33 ± 0.58, and 151.67 ± 1.15; 13.67 ± 1.15, 22 ± 1.00, 40.67 ± 0.58 and 135.67 ± 1.15; and 12.33 ± 0.58, 21.66 ± 1.15, 39.67 ± 1.53 and 129.33 ± 2.51 respectively. Life cycle studies of C. septempunctata revealed that it took 28 ± 2.64, 24.33 ± 0.58 and 23 ± 1.73 days to complete its life cycle while reared on A. craccivora, A. fabae and A. gossypii respectively. The mitochondrial cytochrome c oxidase (COI) gene of the C. septempunctata were sequenced and submitted to the NCBI GenBank (Accession NO.MH 976795.1). The nucleotide composition analysis revealed that the value of A+T (69.3%) was greater than G+C (30.7%). The intraspecific genetic divergence ranged from 0.000 - 0.005. Haplotype analysis showed less genetic diversity (1 mutational step). Phylogenetic analysis by Maximum Likelihood method showed that all the Coccinella species originated from a common major clade and C. septempunctata originated from different regions of the world. The present research may be useful for attempting any biological control program against the aphid pests.